The role of potent thiols in Chardonnay wine aroma. (25th July 2017) - Capone, D.L.; Barker, A.; Williamson, P.O.; Francis, I.L.
Abstract: Background and Aims: Polyfunctional thiols are key aroma compounds in many Sauvignon Blanc wines, but their role in other white cultivars is not clear. Methods and Results: A survey of 106 commercial Australian Chardonnay wines found a high concentration of 3‐mercaptohexan‐1‐ol, 3‐mercaptohexyl acetate, benzyl mercaptan and 4‐mercapto‐4‐methylpentan‐2‐one, with nearly all wines having a concentration of all compounds well above their reported sensory detection threshold, and some having a concentration comparable to that found in highly fruity Sauvignon Blanc wines. Wines were made on a research scale from a set of Chardonnay juices sourced from 16 vineyards across Australia. Sensory descriptive analysis combined with quantitative aroma volatile data revealed that several aroma and flavour attributes were related to the concentration of the thiols. Conclusions: This study provided evidence that substantial flavour in Chardonnay can be contributed by these thiols. Additionally, consumer acceptance data showed that wines with a higher thiol concentration were liked by most consumers. Significance of the Study: This study revealed the importance of polyfunctional thiols in Chardonnay wine.